High resolution FTIR study of 34S16O2: The bands 2ν3,2ν1+ν2 and 2ν1+ν2-ν2; Journal of Molecular Spectroscopy; Vol. 318 - Ulenekov (Ulenikov) O. N. Oleg Nikolaevich; Gromova O. V. Olga Vasilievna; Bekhtereva E. S. Elena Sergeevna; Krivchikova Yu. V. Yuliya Valerjevna; Sklyarova E. A. Elena Aleksandrovna; Buttersack T.; Sydow C.; Bauerecker Z. (S.) H. Zigurd (Sigurd) Hermann (2015, 2015)
Title screen